Assistance of Health Personnel in The Implementation of Calibration Results in Public Hospitals Dr. Iskak Tulungagung: Assistance of Health Personnel in The Implementation of Calibration Results in Public Hospitals Dr. Iskak Tulungagung - Maghfiroh, Anita Miftahul; Yulianto, Endro; Syaifudin (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2023)
Optimal quality of health services depends on the accuracy of medical devices. In an effort to improve quality standards, Dr. General Hospital Iskak Tulungagung implements a program to assist health workers in understanding and applying the results of medical device calibration. This research aims to increase health workers' knowledge about calibration, strengthen patient confidence, and improve the accuracy of diagnosis and treatment. This research contributes to improving the competency of health workers and increasing patient satisfaction through assistance in implementing calibration results. This contribution is important in building public trust in health services. The mentoring program involves regular counseling, practical workshops, skills training, as well as individual mentoring by a team of calibration experts. A feedback system is also implemented for continuous evaluation and improvement. This research shows a significant increase in health workers' understanding of medical device calibration. Patients report higher levels of satisfaction with services provided by healthcare professionals who use calibrated devices. This mentoring program was successful in increasing health workers' understanding of calibration, building patient trust, and increasing the accuracy of diagnosis and treatment. This success indicates the importance of assistance in the context of implementing calibration results in hospitals. The results of this research have positive implications for improving health service quality standards. These implications extend to the health education sector and clinical practice, strengthening evidence-based practice and increasing public trust in the health system. Thus, the mentoring program becomes a viable model for improving the quality of health services in hospitals and other health institutions